Error Estimate of Eigenvalues of Perturbed Higher-Order Discrete Vector Boundary Value Problems - Haiyan Lv; Yuming Shi; Guojing Ren (Abstract and Applied Analysis)
This paper is concerned with the eigenvalues of perturbed higher-order discrete vector boundary value problems. A suitable admissible function space is first introduced, a new variational formula of eigenvalues is then established under certain nonsingularity conditions, and error estimates of eigenvalues of problems with small perturbation are finally given by using the variational formula. As a direct consequence, continuous dependence of eigenvalues on boundary value problems is obtained under the nonsingularity conditions. In addition, two special perturbed cases are discussed.